Updated overview of evidence on optimal antithrombotic therapy in patients with atrial fibrillation undergoing percutanous coronary intervention - Koziński, Marek; Rejszel-Baranowska, Joanna; Młodawska, Elżbieta; Siller-Matula, Jolanta M.; Tomaszuk-Kazberuk, Anna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
Selection of the optimal peri- and postprocedural antithrombotic regimen in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) is a common clinical problem which may pose a challenge to medical practitioners. This systematic review summarizes the updated evidence on this topic. Non-vitamin K oral anticoagulants (NOACs) at standard doses are the preferred option in most of post PCI patients with AF, except those few with a clear indication for a vitamin K antagonist (VKA). Reduced NOAC doses should be considered in dabigatran- or rivaroxaban-treated patients with a high bleeding risk, which prevail over concerns about stent thrombosis or ischemic stroke. There is insufficient evidence to favor one NOAC over another in this setting. In the early post stenting period, triple therapy comprising a NOAC, clopidogrel and aspirin is recommended. Timing of post PCI aspirin cessation should be based on a careful analysis of the bleeding and ischemic risk. There is only low quality evidence regarding the optimal approach to elective or urgent/emergency PCI procedures in patients requiring oral anticoagulation. It is suggested that there is no need of interruption of VKA and PCI procedure should be performed via radial artery access with a lower dose of unfractionated heparin. On the other hand, NOACs are usually stopped before elective PCIs, while urgent/emergency procedures may be performed with the addition of low-dose parenteral anticoagulation.